The role of parecoxib in inhibiting agitation during the awakening period after the extraction of pediatric supernumerary teeth under sevoflurane anesthesia - DONG Yanhai; ZHANG Miao; CUI Zihui; LIU Lan (Kouqiang hemian waike zazhi)
[Objective:] To investigate the influence of dexmedetomidine combined with parecoxib on emergence agitation in children after extraction of supernumerary teeth under sevoflurane anesthesia. [Methods:] A total of 80 children who underwent extraction of supernumerary teeth in the hospital from August 2019 to August 2022 were selected as the research subjects. According to the random number table method, the subjects were divided into combination group and control group. A total of 40 children (combination group) received intravenous injection of dexmedetomidine (0.5 μg/kg) and parecoxib (0.75 mg/kg) at 10 min before anesthesia induction, continuous injection of dexmedetomidine [0.4 μg/(kg·h):] after anesthesia induction till 5 min before the end of surgery, and the other 40 children (control group) received injection of the same dose of normal saline, and injection of dexmedetomidine (0.5 μg/kg) combined with normal saline in the same way. Both groups were mantained under anesthesia with 2% to 4% sevoflurane, and sevoflurane was immediately discontinued upon completion of the surgery. Heart rate (HR), mean arterial pressure (MAP) and pulse oxygen saturation (SpO2) at the time of entering the room (T0), 10 min after prespecified drug infusion (T1), intubation (T2), entering the recovery room (T3), and recovery (T4) were compared between the groups. The recovery time of spontaneous breathing, extubation time, time to leaving recovery room, agitation and sedation during recovery period, and the incidence of adverse reactions were recorded. [Results:] There were statistically significant differences in HR and MAP in terms of time effect, inter-group effect, and interaction effect (P<0.05). From T1—T4, the combination group had lower HR and MAP than the control group (P<0.01). The recovery time of spontaneous breathing and time to leaving recovery room in the combination group were shorter than those in the control group (P<0.05). The pediatric anaesthesia emergence delirium (PAED) scores and the incidence of emergence agitation in the combination group were lower than those in the control group, and the Ramsay sedation scores were higher than those in the control group (P<0.05). The total incidence of adverse reactions showed no significant difference between the groups (P>0.05). [Conclusion:] Dexmedetomidine combined with parecoxib in pediatric supernumerary teeth extraction under sevoflurane anesthesia is beneficial to maintain perioperative hemodynamic stability, shorten recovery time from anesthesia, and inhibit emergence agitation, without increasing adverse reactions.